(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study compared the outcome of students’ performance using the standard setting method with the equivalent outcome they would have obtained using the absolute grading method. It involved the comparison of fail, pass, honors and distinction grades in Digestive System, Endocrine System, Cardiovascular System and Health and the Environment courses in the MBBS Stage I examination. The performance in Cardiovascular System was significantly better with the standard setting method (χ2 = 27.53; p < 0.01), median score in the honors range compared with the absolute grading method where the median score was in the pass range. On the other hand, the performance in Endocrine System was significantly better using the absolute grading method (χ2 = 27.30; p < 0.01), with median score in the honors range compared with the standard setting method where the median score was in the pass range. There was no difference in the performance in Digestive System (χ2 = 7.45; p = 0.06), median score in the pass range and Health and the Environment (χ2 = 6.34; p = 0.09), median score in the honors range; between the standard setting and absolute grading methods (Wilcoxon’s signed rank). The overall pass, honors, distinction and failure rates were also identical in both methods (Mann Whitney U test). This suggests that overall the outcome of the students’ performance in the standard setting method compared with the absolute grading method were not significantly different.